Shear strain energy related to mining induced fault slip and its implications for rockbursts - Yatao Li; Xuehong Gao (Scientific Reports)
Abstract Shear strain energy, a critical factor in the occurrence of earthquakes and rockbursts, plays a vital role in deep mining operations. This study investigates the spatial distribution of shear strain energy (E s) in mining-induced fault coseismic slip and its implications for rockburst risk assessment, offering a novel perspective. We thoroughly explore the dynamics of E s, which are critical to seismic activity and rockburst phenomena in deep mining operations. By integrating advanced numerical simulation techniques with observational data from the F16 fault zone, we analyze the interplay among mining distance (D m), fault cohesion, and their collective impact on E s variations. Our analysis reveals a nuanced understanding of E s in mining induced fault slip, particularly highlighting a marked increase in E s concentrations at the working face as mining approaches the fault. This observation underscores the critical influence of D m on elevating rockburst risks. Additionally, we discover that enhanced fault cohesion contributes to a decrease in E s, thereby mitigating rockburst risks. These insights afford a novel perspective on managing rockburst hazards in deep mining operations, offering theoretical and methodological advancements for predicting and curtailing geological hazards.